2009
DOI: 10.3390/d1020151
|View full text |Cite
|
Sign up to set email alerts
|

Adventive Vertebrates and Historical Ecology in the Pre-Columbian Neotropics

Abstract: The arrival of Europeans in the Western Hemisphere (ca. AD 1500) is generally used as a convenient reference point for signaling the early appearance of invasive faunas. Although use of this date embraces an implicit belief in benign landscape management by pre-Columbian inhabitants of the Americas, substantial evidence for the anthropogenic movement of domesticated, wild, and synanthropic vertebrates throughout the Neotropics suggests that it may be an exaggerated and erroneous reference point for the aims of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 68 publications
(88 reference statements)
0
15
0
Order By: Relevance
“…That turnover in species, which can involve more or less invasive species, is often documented as resulting in a net loss of diversity, often on a large scale because of the dissemination of invasive species and their superior competitive attributes (e.g., [29]), but what we have learned from historical ecology is that primary landscape transformation can sometimes result in net increases in diversity [23]. In either case, regardless of the upward or downward trend in species abundance values, the anthropogenesis of Amazonian landscapes is increasingly documented not only in the living vegetation, but archaeologically in the form of extensive patterns of earthworks [15,16,19,[30][31][32][33][34][35].…”
Section: Primary Vs Secondary Landscape Transformationmentioning
confidence: 99%
“…That turnover in species, which can involve more or less invasive species, is often documented as resulting in a net loss of diversity, often on a large scale because of the dissemination of invasive species and their superior competitive attributes (e.g., [29]), but what we have learned from historical ecology is that primary landscape transformation can sometimes result in net increases in diversity [23]. In either case, regardless of the upward or downward trend in species abundance values, the anthropogenesis of Amazonian landscapes is increasingly documented not only in the living vegetation, but archaeologically in the form of extensive patterns of earthworks [15,16,19,[30][31][32][33][34][35].…”
Section: Primary Vs Secondary Landscape Transformationmentioning
confidence: 99%
“…For example, previous zooarchaeological research in the Caribbean has demonstrated the intentional inter-island transport and introduction of hutias (a medium-sized endemic rodent) from Hispaniola (and/or Cuba) to Puerto Rico, the Bahamas, and possibly the Virgin Islands by Amerindians (Newsom and Wing 2004;Wing 2001Wing , 2012. Furthermore, human agency has also been clearly implicated in the translocation of a wide range of mammalian species from mainland South America into the Antilles in pre-Columbian times (Newsom and Wing 2004;Stahl 2009;Wing 2001Wing , 2008Wing , 2012, including agouti (Newsom and Wing 2004;Wing 2001Wing , 2012, armadillo (Giovas et al 2012;Wing 2012), dog (Grouard 2001;Newsom and Wing 2004;Wing 2008Wing , 2012, guinea pig (LeFebvre and deFrance 2014; Newsom and Wing 2004), opossum (Giovas et al 2012;Grouard 2001;Newsom and Wing 2004;Wing 2012), and possibly also deer and peccary (Giovas et al 2012;Giovas et al 2015). Recently, there has been renewed interest in research pertaining to the presence of nonlocal (mainland) animals and animal remains in the circum-Caribbean.…”
Section: Introductionmentioning
confidence: 99%
“…), and opossum ( Didelphis sp.) (Giovas et al 2011 , 2016 ; also Stahl 2009 ). The extent of deliberate translocations of plant foods is not immediately clear.…”
Section: Human Colonization and Its Biological Effectsmentioning
confidence: 93%